Ecological silviculture: a model for plantations of species of the genus Nothofagus in Chile - Donoso, Pablo; Navarro, Celso; Vásquez-Grandón, Angélica; Larraín, Oscar; González Chang, Mauricio; Romero, Mario; Dumont, Paulo (BOSQUE, 2025)
Commercial forest plantations grow wood and fiber in an efficient manner. These plantations are generally monospecific, grown in short rotations, and clear cut. In many countries, including Chile, these plantations are established with exotic species. Although these plantations will continue expanding in the world, there are also increasing social and ecological demands to establish, or generate, plantations with greater diversity. Ecological silviculture looks after the development of these types of forests that provide timber and multiple ecosystem services, with an emphasis in developing complex and adaptive ecosystems. This article provides ecological silviculture proposals for plantations with Nothofagus dombeyi and Nothofagus alpina. We discuss the conventional model of relatively short rotations and alternative models leading to muti-aged forests that will require supplementary plantations with species of the genus Nothofagus. This model is not meant to discard the conventional plantations, but rather to be present in landscapes with productive purposes, safeguarding diverse ecosystem services in forests with greater adaptive capacity.